TOXIC EFFECTS OF LEAD ON FISH AND HUMAN - Ishaque, A; Ishaque, S; Arif, A; Abbas, HG (Biological and Clinical Sciences Research Journal, 2020)
Bioaccumulation is a characteristic aspect in toxicity caused by Pb exposure. Toxic effects are induced in fish due to Pb exposure effecting its biochemical and physiological functions. Exposure pathway (dietary and waterborne), environmental factors (salt-water or fresh water) and Pb binding capacity with protein, SH and sulfur group decide accumulation pattern of Pb exposure. Activation of antioxidant responses like TBARS, GSH, GST, CAT and SOD occurs in fish for its protection in response to the oxidative stresses induced in fish due to Pb accumulation. Disruption of neurotransmitter function also occurs due to Pb accumulation which causes neurotoxicity in fish. Pb interaction also disturbs immune system responses. In fish, various systems are affected due to Pb toxic exposure which can be used as an indicator of toxicity in aquatic environment.